การพัฒนารูปแบบการมีส่วนร่วมของชุมชนในการจัดการศึกษา นอกระบบและการศึกษาตามอัธยาศัยของ กศน.ตำบล: การประยุกต์ใช้การวิเคราะห์องค์ประกอบเชิงยืนยันและ การวิจัยปฏิบัติการ - ศรีสุรกุล ธีรศักดิ์; ปทุมเจริญวัฒนา วรรัตน์; นิลโมจน์ วิรุฬห์ (Journal of Education Studies, Chulalongkorn University, 2014)
งานวิจัยมีวัตถุประสงค์เพื่อ ๑) ศึกษาตัวบ่งชี้และองค์ประกอบการมีส่วนร่วมของชุมชนในการ จัดการศึกษานอกระบบและการศึ ษาตามอัธยาศัยของ กศน.ตำบล ๒) ตรวจสอบความกลมกลืนของตัว บ่งชี้และองค์ประกอบเชิงทฤษฎีการมีส่วนร่วมของชุมชนในการจัดการศึกษานอกระบบและการศึกษา ตามอัธยาศัยของ กศน.ตำบลที่ผู้วิจัยพัฒนาขึ้นกับข้อมูลเชิงประจักษ์ ๓) พัฒนารูปแบบการมีส่วนร่วมของ ชุมชนในการจัดการศึกษานอกระบบและการศึกษาตามอัธยาศัยของ กศน.ตำบลและ ๔) จัดทำข้อเสนอเชิง นโยบายการมีส่วนร่วมของชุมชนในการจัดการศึกษานอกระบบและการศึกษาตามอัธยาศัยของ กศน.ตำบล ผลการวิจัย พบว่า ๑) การมีส่วนร่วมของชุมชนในการจัดการศึกษานอกระบบและการศึกษาตามอัธยาศัย ของ กศน.ตำบลประกอบไปด้วยองค์ประกอบ ๕ ด้าน ๑๕ ตัวบ่งชี้ ๒) ผลการตรวจสอบความกลมกลืนของตัว บ่งชี้และองค์ประกอบเชิงทฤษฎีการมีส่วนร่วมของชุมชนในการจัดการศึกษานอกระบบและการศึกษา ตามอัธยาศัยของ กศน.ตำบลที่ผู้วิจัยพัฒนาขึ้นมีความสอดคล้องกับข้อมูลเชิงประจักษ์ (χ2/df = 1.97, RMSEA = 0.06, SRMR = 0.04, NFI = 0.93, GFI = 0.93, PGFI = 0.57) ๓) รูปแบบการมีส่วนร่วม ของชุมชนในการจัดการศึกษานอกระบบและการศึกษาตามอัธยาศัยของ กศน.ตำบลคือการที่ผู้มีส่วนร่วม ในชุมชนเข้ามามีส่วนร่วมในการจัดการศึกษานอกระบบและการศึกษาตามอัธยาศัยของ กศน.ตำบลตาม องค์ประกอบ ๕ ด้าน ๔) ข้อเสนอเชิงนโยบายการมีส่วนร่วมของชุมชนในการจัดการศึกษานอก ระบบและการศึกษาตามอัธยาศัยของ กศน. ตำบลมีความเหมาะสม (ค่าเฉลี่ย ( X ) ระหว่าง ๓.๙๒ ถึง ๔.๐๘) และความเป็นไปได้(ค่าเฉลี่ย ( X ) ระหว่าง ๔.๐๐ ถึง ๔.๓๑) ในการนำไปสู่การปฏิบัติ The aims of the research were to: 1) identify the indicators and factors of community participation in organizing non-formal and informal education for sub-district non-formal education centers; 2) examine the appropriate integration of indicators and conf irmatory factors of community participation in organizing non-formal and informal education for sub-district non-formal education centers for which the researcher developed the theory from the empirical data; 3) develop a community participation model in organizing non-formal and informal education for sub-district non-formal education centers; and 4) propose policy recommendations for community participation in organizing non-formal and informal education for sub-district non-formal education centers. The results were as follows: 1) Community participation in organizing non-formal and informal education for sub-district non-formal education centers consisted of 5 factors and 15 indicators. 2) The results of the examination of the appropriate integration of indicators and conf irmatory factors of community participation in organizing non-formal and informal education for sub-district non-formal education centers for which the researcher developed the theory from the empirical data were in accordance with the data (χ2/df = 145.75, RMSEA = 0.06, SRMR = 0.04, NFI = 0.93, GFI = 0.93, PGFI = 0.57). The weight value of those 15 indicators werereviewed as positive (between the range of 0.69 to 0.91). 3) The development of a community participationmodel in organizing non-formal and informal education for sub-district non-formal education centers def ined as the participation of community members in organizing non-formal and informal education for sub-district non-formal education centers based on the 5 factors. 4) Policy recommendations were at an appropriate score (mean ( X ) between 3.92 to 4.08) and probability score (mean ( X ) between 4.00 to 4.31) in the implementation.